Regarding the Russia’s Role as a Traditional Capital Exporter in the Modern Context - LAVRENTEVA, Larisa Victorovna; GURTOVAYA, Nataliia Sergeevna; VINNIKOVA, Irina Sergeevna; KUZNETSOVA, Ekaterina Andreevna; OGORODOVA, Marina Viktorovna (Journal of Advanced Research in Law and Economics, 2017)
All countries export and import capital at different scales. Capital in foreign countries is imported, exported and functions. Indirect and direct investments represent capital exported in the business form. Russia undertook its foreign economic expansion at the end of the 19th century and since then it has been an active capital exporter for over a century.
Keywords: capital; import; export; investment; exporter